Beyond 11% Efficiency: Characteristics of State‐of‐the‐Art Cu2ZnSn(S, Se)4 Solar Cells. Issue 1 (16th August 2012) - Todorov, Teodor K.; Tang, Jiang; Bag, Santanu; Gunawan, Oki; Gokmen, Tayfun; Zhu, Yu; Mitzi, David B.
<x xml:space="preserve">Abstract</x> A world‐record CZTSSe device is reported, surpassing 11% power conversion efficiency for the first time. The results reflect not only higher efficiency, but also other improved device characteristics, such as fill factor and short circuit current. The improvement in CZTSSe devices continues to point to significant promise for the kesterite‐based absorbers. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>